Pembinaan Karakter Toleransi Siswa SMP Negeri 1 Sultan Daulat - Salmudin Salmudin; Mukhsin Nyak Umar; Yusra Jamali (Tadabbur: Jurnal Peradaban Islam, 2023)
This study aims to: 1) Know the concept of fostering the character of tolerance for students of SMP N 1 Sultan Daulat, Subulussalam City. 2) Knowing the implementation of tolerance character building for students of SMP N 1 Sultan Daulat, Subulussalam City. 3) Find out the follow-up of tolerance development for students of SMP N 1 Sultan Daulat, Subulussalam City. In this study, researchers used a qualitative research approach. Data collection techniques used are: Observation, Interview, Study documentation, Focus groups, Participation. The results of this study are: The results of this conclusion are: 1) The concept of fostering the character of tolerance which is applied in SMP Negeri 1 Sultan Daulat, includes: Values Education, Interreligious and Intercultural Dialogue, Project-Based Learning joint problem groups, Simulations and Games Roles between students, Community Service Program, Development of Social Awareness, Collaborative Learning by Encouraging students to work together among students in groups, Excellence-Based Learning. 2) The application of tolerance character development for SMP N 1 Sultan Daulat students is not an obstacle in the application of the values of religious education. Teachers have a high awareness to respect students' religious differences and try to understand their needs in learning. Teachers also strive to create an inclusive and welcoming environment for all students, regardless of their religion or background. 3) Follow-up to fostering the character of tolerance for students of Sultan Daulat 1 Public Middle School can be carried out through several steps and activities, including: Implementation of Tolerance Values in the Curriculum, Formation of Tolerance Committees, Teacher Training Providing training and coaching to teachers, Extracurricular Activities and Projects Tolerance, Conducting outreach and campaigns in the school environment, Leadership Development, Conducting periodic evaluations of the results and impacts of tolerance character building carried out.